The assessment of labor induction efficacy in inpatient department - D.L. Guryev; M.B. Okhapkin; D.D. Guryeva; I.V. Kabanov; M.S. Gureva; L.N. Nidershtrat; T.A. Sorokina (LCC «Medicine-Inform», 2020)
D.L. Guryev1,2, M.B. Okhapkin2, D.D. Guryeva2, I.V. Kabanov2, M.S. Gureva1, L.N. Nidershtrat1, T.A. Sorokina1 1Regional Perinatal Center, Yaroslavl, Russian Federation 2Yaroslavl State Medical University, Yaroslavl, Russian Federation Aim: to assess the efficacy of labor induction using similar techniques in various groups, to determine the groups of pregnant women with the best and the worst response to labor induction, and to identify clinical anamnestic factors which reduce the efficacy of labor induction in certain groups of pregnant women. Patients and Methods: retrospective analysis of delivery case histories of 765 women admitted to the Regional Perinatal Center was performed. All women underwent labor induction according to the protocol "Cervical ripening and labor induction" developed in 2013. All women were subdivided into the groups applying a 10-group classification system of the efficacy of labor induction developed by T.A. Nippita. Labor induction was considered to be effective in case of vaginal delivery in the lack of perinatal mortality and severe postnatal asphyxia. Results: cephalic, term (39-40 weeks), multiparous women comprised the largest group (n=211, 27.6%) while non-cephalic women comprised the least group (n=16, 2.1%). Cesarean section rate following labor induction  was maximum (n=22, 44%) in women after one previous cesarean and minimum (n=1, 4.5%) in women with multiple pregnancy. In the Regional Perinatal Center, the rate of cesarean section was 15.5% following labor induction and 20.7% without labor induction. In T.A. Nippita Center, the rate of cesarean section following labor induction was 21.0%. The rate of severe postnatal asphyxia was 5.4‰ following labor induction and 6.5‰ without labor induction (р=0.94). No postnatal mortality following labor induction was reported. Conclusions: labor induction in the Regional Perinatal Center should be considered as effective. Repeat births, cephalic presentation, more than 38 weeks of pregnancy, and multiple pregnancy improve the efficacy of labor induction. Less cervical ripening, breech presentation, and previous cesarean section reduce the efficacy of labor induction. 10-group classification system developed by T.A. Nippita provides objective analysis of the efficacy of labor induction in various groups of pregnant women to compare these findings with data derived from other institutions. Keywords: labor induction, risk factors, efficacy classification system, rate of cesarean section, natural birth. For citation: Guryev D.L., Okhapkin M.B., Guryeva D.D. et al. The assessment of labor induction efficacy in inpatient department. Russian Journal of Woman and Child Health. 2020;3(1):-15. DOI: 10.32364/2618-8430-2020-3-1-9-15.